2017
DOI: 10.1007/s10792-017-0488-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intraocular pressure, anterior chamber depth and lens thickness in primary open-angle glaucoma patients

Abstract: ACD is shallower in females. There is no significant correlation between IOP and ACD or between IOP and LT in POAG as well as normal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
6
2
Order By: Relevance
“…15 As no significant correlation between IOP and ACD has been shown among POAG cases before, the higher IOP values of our JOAG cases should not contribute to this ACD difference. 16 No significant differences in LT, K values, or WTW values were detected in our study. We measured these parameters before antiglaucoma treatment and excluded patients with previous anti-glaucoma treatment because these agents may affect the structure of the anterior segment.…”
Section: Discussioncontrasting
confidence: 63%
“…15 As no significant correlation between IOP and ACD has been shown among POAG cases before, the higher IOP values of our JOAG cases should not contribute to this ACD difference. 16 No significant differences in LT, K values, or WTW values were detected in our study. We measured these parameters before antiglaucoma treatment and excluded patients with previous anti-glaucoma treatment because these agents may affect the structure of the anterior segment.…”
Section: Discussioncontrasting
confidence: 63%
“…Because the IOP-induced compressive strain in the LC was relatively low (up to 2.5%), it therefore makes sense that microcapillaries would not be affected that much by such deformations. It also means that an elevated pressure range normally observed in glaucoma patients (25-35 mm Hg 53 ) would have minimal effects on the average LC oxygen concentration. Despite the small impact that an elevated IOP had on the oxygen concentration, this effect may become significant over a long progression period of glaucoma disease.…”
Section: Discussionmentioning
confidence: 99%
“…There was a weak positive correlation of 0.13 which was statistically significant. Adewara et al (2017) conducted a study which showed that the mean ACD in the control group was higher than in the control group. The difference was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%